ENVIRONMENTAL CRISIS AND ECOCRITICISM IN "MIDNIGHT'S CHILDREN": READING THE NOVEL THROUGH AN ENVIRONMENTAL LENS (International Journal of Food and Nutritional Sciences, 2022)
This paper applies an ecocritical framework to analyze how Salman Rushdie's novel Midnight's Children weaves environmental concerns into its exploration of India's tumultuous history. Through close readings of key passages and characters, the analysis examines how Rushdie intertwines ecological degradation with socio-political narratives. The novel's use of magical realism allows for the portrayal of trauma, particularly through the character Saleem, who experiences the traumas of Partition. The research probes into how Rushdie's work reveals a concern for environmental degradation, especially in urban areas and metropolitan cities. Midnight's Children contains direct descriptions of toxicity and pollution and can be seen as a condemnation of the complexities generated by modern civilization that have led to the current ecological crisis. The Sundarbans, a mangrove forest region in the Bay of Bengal, features prominently in the novel and is used to explore postcolonial Indian identity in relation to the natural environment. The novel suggests that finding one's identity and place in the world requires an understanding of one's relationship to nature and the environment. This ecocritical approach sheds light on the environmental crisis as a metaphor for the challenges of postcolonial identity and nation-building. By examining how Rushdie weaves environmental elements into the story and how characters interact with their surroundings, the analysis illuminates the novel's commentary on environmental degradation, human-nature relationships, and broader socio-cultural issues within the context of postcolonial India